Percepção ambiental do risco químico e ocorrências de metais pesados no lago Iripixí, Oriximiná-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
One of the central aspects of the discussion of natural resource pollution stems from the increasing exposure of natural and human environments to nonpolar chemical compounds such as toxic metals and pesticides. In the municipality of Oriximiná- PA due to urban expansion and agricultural activities on the shores of Lake Iripixí ecotoxicological studies can be used as instruments to defend environmental and human health. The objective of this work was to evaluate the environmental perception of the residents around Lake Iripixí regarding the exposure of pesticides and toxic metal occurrences in relation to the environment and public health. Data collection was done by applying a semi-structured questionnaire, closed and open. Water and sediment samples were analyzed using the ICP-OES Plasma Optical Emission Spectrometry method. The data obtained were analyzed with statistical tool described by ANOVA and Tukey's test procedure allows for the formation of 100 (1 -α). In addition to the multivariate statistical analysis (cluster) to describe the similarity between the samples considering the total set of variables and the correlations between these variables. According to the data, the description of the environmental problems listed by the residents around the Iripixi lake, Oriximiná-PA, were 50% sewage; silting 26.08%; deforestation 2.17%; pesticide 4.34%; eutrophication 2.17% and another 15.21%. Lack of sanitation is the biggest environmental problem in the region where they live. The levels of toxic metals, Cd, Cr, Cu, Ni, Pb and Zn in the sediment are within the reference values established by the Brazilian legislation, however the values for water are above the recommended for surface waters in the Amazon. Exposure to chemical residues has caused severe effects, whether acute or chronic, on several workers, especially those in rural areas. Important strategies must be implemented to minimize exposure of these people, as the low education level of the sample population leads to poisoning due to considerable use of chemicals. pesticides, due to inappropriate use of PPE and inefficient policies regarding the handling of certain chemicals. The presence of heavy metals in Lake Iripixi water above what Brazilian law allows suggests efficient policies regarding urban disordered growth within the lake, thus reducing the discharge of domestic effluents; and anthropic activities around the lake, as well as controlling non-point agricultural pollution to mitigate environmental and human hazards associated with toxic metals.
Keywords: Lagos urbanos; Contaminantes; Risco; Pesticidas; Metais pesados; CNPQ::CIÊNCIAS DA SAÚDE::FARMÁCIA::TECNOLOGIA FARMACÊUTICA; Toxicologia ambiental; Fisiologia Ambiental